Differential Regulation of PIWI-LIKE 2 Expression in Primordial Germ Cell Tumor Cell Lines by Promoter Methylation - Giebler, Maria; Greither, Thomas; Behre, Hermann M. (Frontiers in Genetics, 2018)
Abstract PIWI-LIKE 2, a member of the Argonaute protein family, is exclusively expressed in pre-pachytene and pachytene stages of spermatogenesis. PIWI-LIKE 2 acts in the germ cell development and the silencing of retrotransponsons to maintain the genomic integrity and stem cell character. In the present study we investigated DNA methylation as potential mechanism for the regulation of human PIWI-LIKE 2 expression in cell lines related to spermatozoa precursor cells. We detected a high methylation of the PIWI-LIKE 2 promoter in TCam-2 cells, while in NT2/D1 cells the promoter was hypomethylated. Concordantly, PIWI-LIKE 2 expression is higher in NT2/D1 cells than in TCam-2 cells. By demethylation of the promoter with 5’-Azacytidin, PIWI-LIKE 2 expression in TCam-2 was increased, while in NT2/D1 no alterations in PIWI-LIKE 2 expression could be detected. In conclusion, we analyzed the epigenetic mechanisms driving PIWI-LIKE 2 expression in undifferentiated germ cell tumors and demonstrated an epigenetic basis for PIWI-LIKE 2 expression in this cell type.